'Common But Differentiated Responsibilities' in the National Courts: Lessons from Urgenda v. The Netherlands. Issue 2 (24th October 2016) - Ferreira, Patrícia Galvão
Abstract: The landmark 2015 decision by the Hague District Court in Urgenda v. The Netherlands represents the first time a national court has expressly used the international environmental law (IEL) principle of common but differentiated responsibilities and capabilities (CBDRs) of the climate regime as a complementary tool to interpret the scope of a state's climate obligations under domestic law. This article highlights that despite the marked engagement of national courts with IEL in recent decades (including engaging with principles such as sustainable development, polluter pays, intergenerational equity, and precaution), until this decision CBDRs had remained outside the purview of environmental law jurisprudence at the national level. The article examines how the Hague Court used CBDRs to help address two common barriers to climate liability: causation and the 'political question' doctrine. The article argues that the Court was able to find normative content in a core element of the climate-related CBDRs: the 'leadership' role of developed countries in climate action. This core element has remained remarkably consensual throughout the contested history of CBDRs in the climate regime – a history that has gained a new chapter with the signature of the Paris Agreement in December 2015. The article concludes that Urgenda v. The Netherlands may serve as a starting point for a more productive and extensive use of CBDRs in climate litigation, provided litigants make more explicit use of the persuasive authority of the principle.